A Syntactic Analysis of Sentence Structure on Aesop's Fairy Tales - Octavia, Dinda; Setia, Eddy; Nasution, Ely Hayati (RADIANT: Journal of Applied, Social, and Education Studies, 2022)
This study aims to analyze the sentence structures of fairy tales. It was designed with a descriptive qualitative research to Aesop’s fairy tales entitled The Lion and The Mouse and The hare and The Tortoise as the data source and by applying the method of rewriting rules in the tree diagram analysis of syntactical theory, called PSG (Phrase-Structure Grammar). The study took 26 data in which 13 sentences were taken directly from The Lion and The Mouse and the other 13 sentences were taken from The Hare and The Tortoise. The data focused on analyzing the five types of sentence structure based on Burton’s theory including Noun Phrase, Verb Phrase, Adjective Phrase, Adverbial Phrase and Prepositional Phrase. The results showed that the noun phrase uses were found more dominant than the other types of sentence structure with the percentage 38%.